PENGARUH PENGGUNAAN MEDIA CANVA INTERAKTIF DALAM MODEL PEMBELAJARAN EKSPOSITORI TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 264 PADAELO - Abd. Kadir A; Firdaus; Andi Abdul Malik (STKIP Subang, 2026)
This study aims to determine the effect of using interactive Canva media in an expository learning model on improving IPAS learning outcomes of fourth-grade students at SD Negeri 264 Padaelo. The study was motivated by the low IPAS learning outcomes of students and the limited use of interactive digital media in classroom learning. This research employed a quantitative approach with a pre-experimental type using a one group pretest-posttest design. The population consisted of all fourth-grade students at SD Negeri 264 Padaelo in the 2025/2026 academic year, and the sample included 18 students selected through saturated sampling. Data were collected using multiple-choice tests administered before and after the treatment. The data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test with IBM SPSS Statistics 26. The findings showed that the mean pretest score was 59.72, categorized as low, while the mean posttest score increased to 78.61, categorized as high. The Wilcoxon test obtained a significance value of 0.001 < 0.05, indicating a significant difference between pretest and posttest scores. Thus, interactive Canva media in an expository learning model significantly improved students' IPAS learning outcomes.